METHOD OF SIMULTANEOUS OPTIMIZATION OF RADIO DEVICES PERFORMANCE IN FREQUENCY AND TIME DOMAINS - A. V. Smirnov (Российский технологический журнал)
A new method of searching for optimal transfer functions of radio circuits and devices was developed. This method allows optimizing performance in the frequency and time domain simultaneously. These tasks cannot be solved by analytical methods. The searching was performed in the coordinatespace of transfer function poles and zeros. The heuristic algorithm of multistart local search type was applied. Computation of transfer function, gain and transient response and goal function was implemented at each step of local search. In order to compute transient response the state space method was employed. This method provides robustness to rounding errors. The proposed method has the advantages of universality and flexibility due to the fact that it allows varying the set of quality parameters and their weighted coefficients in the goal function. Another advantage of this method is its capability of searching a set of Paretooptimal solutions, from which we can select the most suitable one. Some examples of the transient function optimization under conditions of gain-frequency response in the stop-band are considered. The found approximations have performance exceeding that of the Bessel and Butterworth filters.